2016
DOI: 10.1371/journal.pmed.1002090
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Environmental Risk for Chronic Pain and the Contribution of Risk Variants for Major Depressive Disorder: A Family-Based Mixed-Model Analysis

Abstract: BackgroundChronic pain is highly prevalent and a significant source of disability, yet its genetic and environmental risk factors are poorly understood. Its relationship with major depressive disorder (MDD) is of particular importance. We sought to test the contribution of genetic factors and shared and unique environment to risk of chronic pain and its correlation with MDD in Generation Scotland: Scottish Family Health Study (GS:SFHS). We then sought to replicate any significant findings in the United Kingdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 38 publications
7
47
0
1
Order By: Relevance
“…Consistent with previous studies from our group, we found strong evidence to support a shared genetic aetiology of pain with psychological traits, indicating a vulnerability to depression and other negative mood states (42,43). In addition, we found a negative correlation with factors associated with a longer duration of education.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies from our group, we found strong evidence to support a shared genetic aetiology of pain with psychological traits, indicating a vulnerability to depression and other negative mood states (42,43). In addition, we found a negative correlation with factors associated with a longer duration of education.…”
Section: Discussionsupporting
confidence: 91%
“…MCP showed moderate positive genetic correlation with a range of psychiatric disorders including MDD, SCZ, and PTSD, along with traits anxiety and neuroticism. The magnitude of genetic correlation between MCP and MDD was similar to that shown for von Korff chronic pain grade (a chronic pain phenotype) and MDD by McIntosh et al via a mixed-modelling approach (ρ = 0.53) (McIntosh et al, 2016). This is in line with previous observations of association and indicates that shared genetic risk factors exist between MCP and a range of psychiatric disorders, most notably MDD, and that the genetic correlation between MCP and MDD matches with that between MDD and von Korff CPG, a validated chronic-pain questionnaire-derived phenotype (Von Korff et al, 1992).…”
Section: Genetic Correlationssupporting
confidence: 82%
“…Chronic pain and chronic pain disorders are often comorbid with psychiatric and neurodevelopmental disorders (Gureje et al, 2008). This has been observed for Major Depressive Disorder (MDD) (Nicholl et al, 2014;McIntosh et al, 2016), post-traumatic stress-disorder (PTSD) (Shipherd et al, 2007;Dunn et al, 2011;Phifer et al, 2011;Outcalt et al, 2015;Akhtar et al, 2018), schizophrenia (Watson, Chandarana and Merskey, 1981;de Almeida et al, 2013;Engels et al, 2014) and bipolar disorder (BD) (Nicholl et al, 2014;Stubbs et al, 2015). There are also reported differences in the perception of pain and interoception (sensing and integration of bodily signals) for people with schizophrenia (Lévesque et al, 2012;Urban-Kowalczyk, Pigońska and Śmigielski, 2015), anorexia nervosa (AN) (Strigo et al, 2013;Bär et al, 2015;Bischoff-Grethe et al, 2018) and autism spectrum disorders (ASD) (Clarke, 2015;Gu et al, 2018), with some evidence of an increase in pain thresholds for AN and ASD.…”
Section: Genetic Correlationsmentioning
confidence: 98%
See 1 more Smart Citation
“…These traits are known to often co-occur with BP and twin studies have suggested that they share underlying genetic factors 17 , with similar genetic correlations also seen for other pain phenotypes. [55][56][57] Our results confirm a recent twin report of genetic correlation of sleep disturbance with BP. 58 Overall, the analysis of genetic correlations provides evidence for shared molecular pathways underlying BP and traits considered as BP risk factors, thus providing basis for identification of causal links between them.…”
Section: Discussionsupporting
confidence: 90%